2017
DOI: 10.1136/bmjgh-2017-000434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of removing the barrier of transportation costs on surgical utilisation in Guinea, Madagascar and the Republic of Congo

Abstract: Background81 million people face impoverishment from surgical costs every year. The majority of this impoverishment is attributable to the non-medical costs of care—for transportation, for food and for lodging. Of these, transportation is the largest, but because it is not viewed as an actual medical cost, it is frequently unaddressed. This paper examines the effect on surgical utilisation of paying for transportation.MethodsA hierarchical logistic regression was performed on 2692 patients presenting for surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 28 publications
(18 reference statements)
1
31
0
Order By: Relevance
“…The model was validated against the known population density in Guinea, against demographic parameters for the Guinean population, and against previously-published no-show rates. [14] The model was constructed using the AnyLogic modeling platform (v.8.1.0, St. Petersburg). Data analysis was performed in R (v.3.4.0).…”
Section: Data Analysis and Validationmentioning
confidence: 99%
See 2 more Smart Citations
“…The model was validated against the known population density in Guinea, against demographic parameters for the Guinean population, and against previously-published no-show rates. [14] The model was constructed using the AnyLogic modeling platform (v.8.1.0, St. Petersburg). Data analysis was performed in R (v.3.4.0).…”
Section: Data Analysis and Validationmentioning
confidence: 99%
“…[12,13] Simply offering free surgery is insufficient: patients often continue to report cost barriers, even with free surgery. [14] A recent retrospective study of surgery at a charitable institution in three sub-Saharan African countries, where the majority of the population lives in rural settings, demonstrated that non-medical costs and a lack of transportation were a major barrier to care access. Controlling for confounders, patients seeking care at this institution, which provides surgery itself for free, had a no-show rate of 28% if transportation was not paid for.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was a collaboration between the non‐governmental organization Mercy Ships, the Benin Ministry of Health and the academic institution, King's College London. Mercy Ships visits countries at the invitation of the Head of State, typically spending 10 months delivering free operations and training in partnership with the Ministry of Health, aiming to strengthen the surgical ecosystem, and advocate access to safe affordable timely surgery and development of national surgical plans.…”
Section: Methodsmentioning
confidence: 99%
“…Transportation costs are one of the most important barriers to seeking surgical care. The second research paper in this supplement, by Shrime and colleagues, 5 shows that ‘when transportation costs are paid for, the surgical no-show rate drops by approximately half’. This important study identifies the need to include transportation costs as part of medical costs and appropriately suggests that all types of surgical service providers should subsidise or eliminate transportation costs.…”
mentioning
confidence: 99%